PERBEDAAN ANTARA HASIL BELAJAR DAN MINAT DALAM PENGGUNAAN MEDIA PEMBELAJARAN ONLINE PADA PELAJARAN IPS SISWA KELAS IV SD ISLAM KHAIRU UMMAH KECAMATAN MANGGALA KOTA MAKASSAR - Lirmawati; Idawati; Sulfasyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Differences in learning outcomes in the use of online learning media in social science learning subjects lessons were conducted by Idawati and Sulfasyah. The study described in this article is designed to find out the differences between interests and learning outcomes through online learning media in social science learning subjects for students at the fourth-grade level of SD Islam Khairu Ummah, Manggala in Makassar. The study was aquantitative research with a quasi-experimental study and the design used a quasi-experimental design in which experimental class A was treated by using WhatsApp and experimental class B was treated by using Google Classroom. The samples used in the study were 52 fourth-grade students ofKhairu Ummah Islamic Elementary School Manggala in Makassar. The results indicated that (1) there were differences in students’ learningoutcomes through online learning media by using google classroom and WhatsApp in which the learning outcomes that came from the experimentalclass A average value was 69.6 and the experimental class B was 75.38. (2) During conducting students’ learning activities, the students have a good involvement. Students’ involvement could be seen when students paid attention, dared to express opinions and asked questions, did assignments, and were enthusiastic while learning ran down.